1990
DOI: 10.18174/njas.v38i3b.16577
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategy during pregnancy for ewes with a large litter size. 2. Effect on blood parameters and energy status.

Abstract: In 6 feeding trials with pregnant ewes, blood glucose concentrations were affected by litter size after day 84 of pregnancy. An increase in litter size decreased blood glucose during the last phase of pregnancy. At day 141 a sharp increase in glucose was seen. Ewes with ketosis had after day 126 of pregnancy a significant lower glucose concentration. beta -Hydroxybutyrate (BHB) and non-esterified fatty acids (NEFA) were also affected by litter size in the last months of pregnancy. With increasing litter size B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They suggested that this reduction in intake with larger litter sizes was potentially explained by; reduce abdomen space due to rapid uterine expansion, greater heat stress from more lambs in the uterus especially in ewes with an intact fleece, higher levels of oestrogen which has been shown to reduce intake, and a ewe in an energy deficit state is driven to energy mobilisation resulting in increased levels of free fatty acids which could result in reduced intake. Everts (1990b) and Fogarty et al (1992) reported that glucose levels were negatively affected by litter size after mid-pregnancy. In addition, triplet-bearing ewes in late pregnancy display higher ketone, Beta-hydroxybutyrate (BHB) and non-esterified fatty acid (NEFA) concentrations than twin-bearing ewes (Barlow et al 1987;Morris and Kenyon 2004;Corner et al 2008;Kenyon et al 2010aKenyon et al , 2010b.…”
Section: Lamb Growthmentioning
confidence: 99%
“…They suggested that this reduction in intake with larger litter sizes was potentially explained by; reduce abdomen space due to rapid uterine expansion, greater heat stress from more lambs in the uterus especially in ewes with an intact fleece, higher levels of oestrogen which has been shown to reduce intake, and a ewe in an energy deficit state is driven to energy mobilisation resulting in increased levels of free fatty acids which could result in reduced intake. Everts (1990b) and Fogarty et al (1992) reported that glucose levels were negatively affected by litter size after mid-pregnancy. In addition, triplet-bearing ewes in late pregnancy display higher ketone, Beta-hydroxybutyrate (BHB) and non-esterified fatty acid (NEFA) concentrations than twin-bearing ewes (Barlow et al 1987;Morris and Kenyon 2004;Corner et al 2008;Kenyon et al 2010aKenyon et al , 2010b.…”
Section: Lamb Growthmentioning
confidence: 99%